Trauma and sporadic desmoid tumor development - an approach toward real incidence and aspects of causality - Hohenberger, Peter; Menge, Franka; Hohenberger, Ralph; Kasper, Bernd; Marx, Alexander; Haller, Florian; Baumgarten, Christina; Wardelmann, Eva; Jakob, Jens (Cancer, 2024)
Objectives The development of desmoid tumors (DT) is associated with trauma, which is an aspect with medicolegal relevance. The objective of this study was to analyze the proportion and type of trauma (surgical, blunt/fracture, implants), its lag time, and mutations of the CTNNB1 gene in patients with sporadic DT. Methods We analyzed a prospectively kept database of 381 females and 171 males, median age at disease onset 37.7 years (females) and 39.3 years (males) with a histologically confirmed DT. Patients with germline mutation of the APC gene were excluded. Details of the history particularly of traumatic injuries to the site of DT were provided by 501 patients. Results In 164 patients (32.7%), a trauma anteceding DT could be verified with a median lag time of 22.9 months (SD, 7.7 months; range, 9-44 months). A prior surgical procedure was relevant in 98 patients, a blunt trauma in 35 patients, a punctuated trauma (injections, trocar) in 18 patients, and site of an implant in 10 patients. In 220 patients, no trauma was reported (43.9%), and 58 females (11.6%) had a postpregnancy DT in the rectus abdominis muscle. In 42 patients (8.4%), data were inconclusive. The distribution of mutations in the CTNNB1 gene (codon 41 vs. 45) was similar in patients with and without a history of trauma before DT development. Conclusions A significant subgroup of patients suffers from a trauma-associated DT, predominantly at a prior surgical site including implants to breast or groin, accounting for 77.9% of the cases, whereas blunt trauma was responsible in 22.1%. We found no data to support that trauma-associated DT have different molecular features in the CTNNB1 gene.
Vorab online veröffentlicht: 26 September 2023
Gesehen am 08.11.2023